GAMBARAN HASIL PEMERIKSAAN FUNGSI PARU DAN FAKTOR RISIKO GANGGUAN FUNGSI PARU PADA PEMANGKU DI KECAMATAN DENPASAR TIMUR - Pradnyana, Dewa Gede Putra Angga; Muliarta, I Made (E-Jurnal Medika Udayana; vol 4 no 9(2015):e-jurnal medika udayana, 2015)
CHARACTERISTICS AND RISK FACTORS OF LUNG FUNCTION IMPAIRMENT AMONG HINDU’S PRIEST IN DENPASAR TIMUR DISTRICT   Impaired lung function is a problem that occurs all over the world especially in the developing countries. Impaired lung function can be divided into three kinds, namely restrictive, obstructive, and mixed. Incense smoke is one of the risk factors associated with lung function impairment, especially on priests in Bali. There are two risk factors in priest associated with impaired lung function, i.e. length of time he/she work as priests, as an indicator of duration of exposure, and smoking habits. This study aims to determine the relationship between these risk factors with impaired lung function that occurs in Eastern Denpasar District priests. This study uses an analytical method with cross sectional design. Subjects were 47 priests in Eastern Denpasar District. The result showed no significant correlation between the length of working as priests with restrictive lung function (p=0.181) and obstructive lung function (p=0,659). Also there is no significant correlation found between smoking habits and restrictive (p=0,654) or obstructive lung function (p=0,939). Suggestions for priest is to have a routine health check up and another study need to be conducted on a larger scale to get more accurate data of the relationship between risk factors and impaired lung function.
Keywords: Incense smoke; priests; lung function; smoking